Fulvic acid alleviates cadmium-induced root growth inhibition by regulating antioxidant enzyme activity and carbon–nitrogen metabolism in apple seedlings - Yu, Bo; Xue, Xiaomin; Nie, Peixian; Lu, Ninglin; Wang, Laiping (Frontiers in Plant Science, 2024)
Previous studies have determined that fulvic acid (FA) prevents plants from suffering from abiotic stress. However, little is known about the mechanisms for using FA to increase apple trees resistance to Cd toxicity. In order to clarify the mechanism underlying FA alleviation in Cd-induced growth inhibition in apple seedlings. Herein, we treated M9T337 seedlings to either 0 or 30 μM/L Cd together with 0 or 0.2 g/L FA and analyzed the root growth, antioxidant enzyme activities, carbon (C) assimilation, nitrogen (N) metabolism, and C and N transport. The results presented that, compared with CK (without Cd addition or FA spraying application), Cd poisoning significantly inhibited the root growth of apple seedlings. However, this Cd-induced root growth inhibition was significantly alleviated by FA spraying relative to the Cd treatment (Cd addition alone). On the one hand, the mitigation of inhibition effects was due to the reduced oxidative damage by enhancing antioxdiant enzyme (SOD, POD, and CAT) activities in leaves and roots.On the other hand, this growth advantage demonstrated compared to the Cd treatment was found to be associated with the strengthen of photosynthetic performance and the elevation of C and N metabolism enzymes activities. Meanwhile, we also found that under Cd stress condition, the distribution of C and N nutrients in apple seedlings was optimised by FA spraying application relative to the Cd treatment, according to the results of 13 C and 15 N tracing. Conclusively, our results suggested that the inhibitory effect of Cd on apple seedlings root growth was alleviated by FA through regulating antioxdiant capacities and C and N metabolism.